Dreams of an Elsewhere or Aspiring to Stay? Navigating Anxious Youthhood and Migration in Morocco - Radouani, Chaimaa (AUC Knowledge Fountain, 2024)
Migration in Morocco has long been a topic of scholarly and public debate, with a particular emphasis on low-skilled labor migration. Nonetheless, there is still a significant need to figure out the aspirations of educated, skilled youth regarding their desire to move or stay in the country. This thesis investigates the aspirations of educated youth in Casablanca, Morocco, and how they are influenced by the changing dynamics of contemporary Morocco. It addresses youth aspirations and migration by examining the elements affecting their decisions within the context of the country’s current economic, social, and political contexts. The primary focus of this research revolves around introducing the contemporary dynamics in Morocco, particularly how socioeconomic factors shape the aspirations of its educated youth. Key questions include why some Moroccan youth perceive their homeland as a desirable place to build their futures, while others entertain migratory aspirations. Drawing on qualitative ethnographic fieldwork, this study provides a new perspective, exposing the nuances of youth aspirations beyond the prevalent migration discourse. The lack of scholarly attention to the aspirations of skilled individuals in modern Moroccan society motivated this research. Using theoretical frameworks such as vulnerability, mobilization, waithood, wait space, and l- brra, the study explores the challenges and aspirations of Moroccan youth. The findings demonstrate that young Moroccans' aspirations are inextricably tied to the dynamic nature of their country. Some see a bright future for Morocco, fueled by existing possibilities and the flood of foreign investment, while others face severe structural and systemic barriers. These challenges, along with ongoing privatization in critical sectors like health and education, intensify sentiments of uncertainty and vulnerability among young people, particularly those from the lower middle class. In addition, cultural and social norms, especially through a gender lens, determine the migratory goals and experiences of young Moroccans. These findings will be discussed in-depth and in detail in the subsequent sections.